2018
DOI: 10.1074/jbc.ra118.004948
|View full text |Cite
|
Sign up to set email alerts
|

Proteolipid domains form in biomimetic and cardiac mitochondrial vesicles and are regulated by cardiolipin concentration but not monolyso-cardiolipin

Abstract: Cardiolipin (CL) is an anionic phospholipid mainly located in the inner mitochondrial membrane, where it helps regulate bioenergetics, membrane structure, and apoptosis. Localized, phase-segregated domains of CL are hypothesized to control mitochondrial inner membrane organization. However, the existence and underlying mechanisms regulating these mitochondrial domains are unclear. Here, we first isolated detergent-resistant cardiac mitochondrial membranes that have been reported to be CL-enriched domains. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…5f). This aggregation effect was not seen in vesicles devoid of CL, and our previous work has shown that proteins that do not associate with CL do not have this effect on CL aggregation 30 . Additionally, we serendipitously discovered that CL-containing vesicles and elamipretide eventually precipitated when in solution together (Supplemental Fig.…”
Section: Effects Of I/r and Elamipretide On H 2 O 2 Emissionmentioning
confidence: 67%
“…5f). This aggregation effect was not seen in vesicles devoid of CL, and our previous work has shown that proteins that do not associate with CL do not have this effect on CL aggregation 30 . Additionally, we serendipitously discovered that CL-containing vesicles and elamipretide eventually precipitated when in solution together (Supplemental Fig.…”
Section: Effects Of I/r and Elamipretide On H 2 O 2 Emissionmentioning
confidence: 67%
“…Using electron spray mass spectroscopy, MLCL was shown to enhance Bid and tBid mitochondrial membrane association, relative to CL [78]. MLCL also appeared to enhance the release of cytochrome c [78] and affect the oxidation state of cytochrome c [79]. Furthermore, MLCL was shown to be capable of inducing tBid dissociation from nBid (the other Bid-cleavage product) [77].…”
Section: Mlcl and Proteins Involved In Apoptosismentioning
confidence: 95%
“…In cultured lymphoblast cells from people with BTHS, apoptosis was found not to be increased [4]. However, MLCL interactions with many proteins involved in apoptosis have been investigated demonstrating that MLCL interacts with tBid more tightly than CL [77,78], caspase-8 [29] less tightly than CL, and also modifies the release of cytochrome c [78,79].…”
Section: Mlcl and Proteins Involved In Apoptosismentioning
confidence: 99%
“…Using a complex mitochondrial inner membrane mimicking model, our lab has also shown that cyt c and mtCK promote proteolipid microdomain formation. These domains are highly sensitive to a decreased CL levels but not substitution of MLCL or (18:1) 4 CL, suggesting that CL content is the more important factor in regulating mitochondrial proteolipid microdomains (161). However, extreme remodeling by the complete incorporation of DHA into CL's acyl chains [(22:6) 4 CL] abolishes proteolipid microdomain organization, which is driven by changes in the Gibbs free energy of lipid mixing (87).…”
Section: Mitochondrial Membrane Microdomain Organizationmentioning
confidence: 99%